Effect of Price Earnings Ratio, Price to Book Value, and Loan to Deposit Ratio on Stock Return (Empirical Study on Banking Companies Listed on the Indonesia Stock Exchange) - Suriany Suriany (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The purpose of this study is to analyze effect of price earnings ratio, price to book value, and loan to deposit ratio on stock return in Banking Companies listed on the Indonesia Stock Exchange. This type of research is quantitative research. The population in this study are Banking Companies on the Indonesia Stock Exchange as many as 44 companies for the period 2013-2017. The sample in this study was 125 consisting of 25 Banking Companies listed on the Indonesia Stock Exchange for 5 periods, namely the period 2013-2017. In this study, the researcher first removed the outlier data, so that the number of samples became 61 samples. This study uses multiple linear regression. The results showed that price earnings ratio has no significant effect on stock return in Banking Companies Listed on the Indonesia Stock Exchange. Price to book value has a significant effect on stock return in Banking Companies Listed on the Indonesia Stock Exchange. Loan to deposit ratio has no significant effect on stock return in Banking Companies Listed on the Indonesia Stock Exchange. Price earnings ratio, price to book value, and loan to deposit ratio have a significant effect on stock return in Banking Companies Listed on the Indonesia Stock Exchange.